Characteristic Seismic Waves Associated with Cryosphere Dynamics in Eastern Dronning Maud Land, East Antarctica - Masaki Kanao; Akira Yamada; Mikiya Yamashita (International Journal of Geophysics)
Several kinds of natural source signals are recorded by seismic exploration stations on the continental ice sheet in Eastern Dronning Maud Land, East Antarctica, during 2002 austral summer. They include not only tectonic earthquakes, but also ice-related phenomena possibly involving recent global climate change. The recorded signals are classified into (1) teleseismic events, (2) local ice quakes, and (3) unidentified events (X-phases). The teleseismic waves show the high signal-to-noise ratio in spite of the small magnitude of the event; this indicates that it is highly feasible to study not only the local shallow structure but also the deep structure of the earth by using teleseismic events. Frequency spectra of the all waveforms represent discordances along the observation seismic profile. The abrupt change of topography in the valley along the seismic profile might cause both the anomalous frequency content and travel times. Finally, an origin of the X-phases is speculated as the intraplate earthquakes or possibly large ice-quakes (glacial earthquakes) around Antarctica, involving global warming appeared in polar region.